A Comparative Analysis of MPPT Techniques for Grid Connected PVs - Kebbab, F. Z.; Sabah, L.; Nouri, H. (Engineering, Technology & Applied Science Research, 2022)
Maximum Power Point Tracking (MPPT) is essential for the application of a photovoltaic (PV) energy system in order to extract the maximum possible power under variable conditions of irradiation and temperature. This paper deals with the implementation of different MPPT algorithms for a PV array installed for a system connected to the Grid: Perturb and Observe (P&O), Fuzzy Logic Control (FLC), Cuckoo Search (CS), and Beta algorithms were simulated in Matlab/Simulink and the results were analyzed and compared. Beta algorithm proved to have greater tracking power, minor power loss, great tracking speed, less time, and less oscillation than the other techniques.